The impact of the preparation and outbreak of a nuclear war on man and his ecosystem - T. Jacob, T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1987)
This article described the medical effects of nuclear arms race and of a probable, intended, unintentional or self-ignited, nuclear war. The danger prior CO and after the explosion of the nuclear arsenal is brought forth. Among the post-war effects the global and prolonged ecological damages are elaborated, affecting both the physical-biological and cultural ecosystem. Considering these effects, post-war survival would not be preferable to immediate death. Medicine would be rendered impotent in such a nuclear holocaust; hence, all efforts have to be concentrated on prevention. Indonesia despite its geographical and political position would not be well off in a total nuclear confrontation. Even here, therefore, the physician as teacher-healer, biologist and scientist or technologist, and especially as a human being, cannot escape the social responsibility to contribute his utmost effort towards the prevention of nuclear war and its preparation. Key Words: medical effects of nuclear war - nuclear winter - human extinction - UV radiation - suppression of immune system